Women Participation in Institutional Management in Nigeria: Challenges and Coping Strategies - Oduwaiye, R. O.; Alabi, A. T. (International Journal of Educational Management, 2022)
With increased awareness on the need to empower women, involvement of women in politics and management of institutions has increased. However, there is still a wide global gap. This paper examines the extent of women’s participation in political systems and educational institutional management. The challenges of gender equity in women’s participation such as time demands, unequal opportunities, sexual harassment, occupational segregation, political under-representation and poverty are examined. For women to be able to cope with these challenges, strategies such as educational empowerment, time management, poverty alleviation and provision of supports are suggested.